2022
DOI: 10.3762/bjnano.13.29
|View full text |Cite
|
Sign up to set email alerts
|

Selected properties of AlxZnyO thin films prepared by reactive pulsed magnetron sputtering using a two-element Zn/Al target

Abstract: AlxZnyO thin films were obtained by reactive pulsed magnetron sputtering. A two-element Zn/Al planar target was used as source material prepared in the form of a Zn disc (100 mm diameter) with Al rings pressed into its surface. The sputtering processes were carried out in a mixture of argon and oxygen. The films were deposited with a discharge power of PE = 400 W, which corresponded to a power density on the target surface of approximately 5 W/cm2. The films were deposited on glass strip substrates, placed sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The self-made disc-type magnetron based on NdFeB magnets (internal N pole and external S pole) that ensures the operation in the balanced mode was mounted at the base of the vacuum chamber. Our previous work [ 5 ] presented the results of studies on the electrical properties, optical properties, chemical composition, and microstructure of AZO thin films prepared using a self-made two-element Zn-Al target. The effect of the position of the substrate in relation to the target and the sputtering conditions was investigated.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The self-made disc-type magnetron based on NdFeB magnets (internal N pole and external S pole) that ensures the operation in the balanced mode was mounted at the base of the vacuum chamber. Our previous work [ 5 ] presented the results of studies on the electrical properties, optical properties, chemical composition, and microstructure of AZO thin films prepared using a self-made two-element Zn-Al target. The effect of the position of the substrate in relation to the target and the sputtering conditions was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that favourable conditions for the formation of TCO layers required placing the substrates at a distance of more than 5 cm from the axis of the target (in a plane 9 cm away from the surface of the target)—the so-called off-axis mode. In contrast to the studies presented in the article [ 5 ], in the present study a commercial high purity target (from ITL Vacuum, 107 mm in diameter and 6 mm thick) with a composition of 99.9%, consisting of 98% by weight ZnO and 2% by weight Al 2 O 3 was used in the present study. The substrates were placed 9 cm in a plane parallel to the target surface and approximately 7.5 cm from the target axis (off-axis mode).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations